[tex]\bf (6n-5)^{\frac{1}{2}}+3=-2\\\\
-----------------------------\\\\
a^{\frac{{ n}}{{ m}}} \implies \sqrt[{ m}]{a^{ n}} \qquad \qquad
\sqrt[{ m}]{a^{ n}}\implies a^{\frac{{ n}}{{ m}}}\\\\
-----------------------------\\\\
thus
\\\\\\
(6n-5)^{\frac{1}{2}}+3=-2\implies \sqrt{6n-5}+3=-2\implies \sqrt{6n-5}=-2-3
\\\\\\
\textit{now squaring both sides}
\\\\\\
(\sqrt{6n-5})^2=(-5)^2\implies 6n-5=25\implies 6n=25+5
\\\\\\
n=\cfrac{25+5}{6}[/tex]
-------------------------------------------------------------------------------------------
[tex]\bf \sqrt{y}-7=0\implies \sqrt{y}=7\impliedby \textit{squaring both sides}
\\\\\\
(\sqrt{y})^2=7^2\implies y=7^2[/tex]